Increased Skeletal Muscle GLUT4 Expression in Obese Mice After Voluntary Wheel Running Exercise Is Posttranscriptional - Gurley, Jami M. (Diabetes, 2016)
Exercise promotes glucose clearance by increasing skeletal muscle GLUT4-mediated glucose uptake. Importantly, exercise upregulates muscle GLUT4 expression in an insulin-independent manner under conditions of insulin resistance, such as with type 2 diabetes. However, the insulin-independent mechanism responsible for rescued muscle GLUT4 expression is poorly understood. We used voluntary wheel running (VWR) in mice to test the prevailing hypothesis that insulin-independent upregulation of skeletal muscle GLUT4 protein expression with exercise is through increased Glut4 transcription. We demonstrate that 4 weeks of VWR exercise in obese mice rescued high-fat diet–induced decreased muscle GLUT4 protein and improved both fasting plasma insulin and hepatic triacylglyceride levels, but did not rescue muscle Glut4 mRNA. Persistent reduction in Glut4 mRNA suggests that a posttranscriptional mechanism regulated insulin-independent muscle GLUT4 protein expression in response to exercise in lean and obese mice. Reduction of GLUT4 protein in sedentary animals upon treatment with rapamycin revealed mTORC1-dependent GLUT4 regulation. However, no difference in GLUT4 protein expression was observed in VWR-exercised mice treated with either rapamycin or Torin 1, indicating that exercise-dependent regulation on GLUT4 was mTOR independent. The findings provide new insight into the mechanisms responsible for exercise-dependent regulation of GLUT4 in muscle.